Venom Audio Customer Loyalty Analysis (Study of Product Quality in the Creative Audio Custom Karawang Team in 2019) - Jumadirrohman, Muhammad Jumadirrohman; Tri Suratmi; Desmiwati, Desmiwati (LPPM Universitas Respati Indonesia, 2023)
PT. Bahagia Audiotama, which owns the Venom audio brand, which was founded in 1998. Venom audio is a car audio brand that has been around for a long time among car audio lovers. Since its inception, it was launched which aims to improve the quality of car audio by presenting a variety of products designed to follow the needs of product users. The purpose of this study was to determine the loyalty of Venom audio product users to the Karawang Creative Audio Custom Team. The sample in this study is 30 people who are an affordable population that can be collected by researchers. Data collection techniques obtained by questionnaire, observation and documentation. The result of this study is that there is a relationship between the independent variables and the dependent variable in this study which was produced by univariate analysis and bivariate analysis. Venom audio can increase product user loyalty by paying attention to aspects that get low scores based on analysis results that can affect product user loyalty Keywords :Product Quality, User Loyalty, Univariate and Bivariate